2023
DOI: 10.1002/oby.23730
|View full text |Cite
|
Sign up to set email alerts
|

Social jet lag and (changes in) glycemic and metabolic control in people with type 2 diabetes

Abstract: Objective: Social jet lag, i.e., the discordance among social and biological rhythms, is associated with poor metabolic control. This study aimed to assess cross-sectional and longitudinal associations among social jet lag and glycemic and metabolic control in people with type 2 diabetes.Methods: In a prospective cohort (N = 990) with type 2 diabetes, social jet lag was measured at baseline using daily diaries and was categorized (high, moderate, or low).Metabolic outcomes were assessed at baseline and at 1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Social jet lag is a subtle and common example of circadian misalignment in modern societies, with a prevalence superior to 50% [ 55 , 141 ]. The clinical impact of social jet lag has been reported in various epidemiological studies [ 141 , 142 ]. Individuals with social jetlag greater than 1 hour have a 1.75 times higher prevalence of diabetes or prediabetes than those with less than 1 hour of social jetlag [ 141 ].…”
Section: Disruptive Circadian Rhythms and T2dmmentioning
confidence: 99%
“…Social jet lag is a subtle and common example of circadian misalignment in modern societies, with a prevalence superior to 50% [ 55 , 141 ]. The clinical impact of social jet lag has been reported in various epidemiological studies [ 141 , 142 ]. Individuals with social jetlag greater than 1 hour have a 1.75 times higher prevalence of diabetes or prediabetes than those with less than 1 hour of social jetlag [ 141 ].…”
Section: Disruptive Circadian Rhythms and T2dmmentioning
confidence: 99%
“…Within‐person deviations in sleep timing over time also are associated with metabolic risk in adults [26]. Adding to this emerging area of research is a paper from Bauman and colleagues showing that greater difference in the timing of sleep between weekends and weekdays, termed social jet lag, was positively associated with hemoglobin A 1c and blood pressure among working adults with type 2 diabetes (T2D) [27]. In contrast, among retired adults with T2D, social jet lag ≥ 2 hours related to favorable glycemic traits despite also being associated with elevated body mass index (BMI).…”
Section: Sleep Timing and Regularity As Predictors Of Metabolic Healt...mentioning
confidence: 99%
“…The study population in Bouman et al 4 (shown in the dashed grey box in Fig. 1 ) has lower social jetlag than younger people (that is, those <60 years old).…”
mentioning
confidence: 96%
“… 3 ). The most recent epidemiological study, by Bouman and colleagues 4 , reports apparently contradicting results that offer explanations on how social jetlag and health might be connected. The authors assessed social jetlag and metabolic and glycaemic outcomes in approximately 1,000 people over the age of 60 with type 2 diabetes mellitus (T2DM), using both a cross-sectional and longitudinal design (re-testing after 2 years).…”
mentioning
confidence: 97%
See 1 more Smart Citation